Does phloem osmolality affect diurnal diameter changes of twigs but not of stems in Scots pine?. (29th October 2018) - Lazzarin, Martina; Zweifel, Roman; Anten, Niels; Sterck, Frank J
Abstract: Diel stem diameter changes measured at the stem base of temperate tree species can be mostly explained by a hydraulic system of flow and storage compartments passively driven by transpiration. Active, osmotic processes are considered to play a minor role only. Here we explore whether such osmotic processes have a stronger impact on diel changes in twig diameter than in stem diameter because twigs are closer to the leaves, the main source of newly acquired carbon. We investigated stem and twig diameter changes of wood and bark of pine trees in parallel to fluctuations of the osmolality in needles and in the bark at the stem base. We found consistent twig bark size increments concurrent with twig wood size decreases during daylight hours whereas needle osmolality was not consistently increasing even on sunny days. The size changes of bark and wood either reversed or ran in parallel from late afternoon onwards until the next morning. No such patterns were measurable at the stem base. Stem wood was hardly changing in size, whereas stem bark followed the regular pattern of a decrease during the daylight hours and an increase during the night. Osmolality at the stem base showed no particular course over 24 h. We conclude that assimilates from the needles were rapidly transported to the twigs where they increased the osmolality of the bark tissue by sugar loading, explaining the bark size increase (over-) compensating the xylem size decrease. The stem base largely followed the expectation of a passive, hydraulic system without a measurable role of osmoregulation. Diameter changes thus follow different diurnal dynamics in twigs and at the stem base.